Guide :

# how to solve: (15x^-1y^2 / 5xy^-4) ^-1

i have no clue on how to work this problem

## Research, Knowledge and Information :

### 15x^2y^2-5xy^2-150y^2= - Get Easy Solution

Simple and best practice solution for 15x^2y^2-5xy^2 ... -5xy 2 + 15x 2 y 2 + -150y 2 = 0 Solving -5xy 2 ... Add '-1y 2 ' to each side of the equation. y 2 + -1y 2 ...
Read More At : www.geteasysolution.com...

### 15x^2y^2-5xy^2-150y^2=0 - Get Easy Solution

Simple and best practice solution for 15x^2y^2-5xy^2 ... -5xy 2 + 15x 2 y 2 + -150y 2 = 0 Solving -5xy 2 ... Add '-1y 2 ' to each side of the equation. y 2 + -1y 2 ...
Read More At : www.geteasysolution.com...

### how to factor y^2+2xy-15x^2? - Weknowtheanswer

how to factor y^2+2xy-15x^2? Answer for ... 15x^2 => y^2 + (5xy - 3xy) - 15x^2 => y*(y + 5x) - 3x ... 150x 2 y 2 = 0 Solving 10 + -20xy + -150x 2 y 2 = 0 Solving for ...

### Can I Have Assistance With Three Problems? 1. (3x^... | Chegg.com

(3x^2y-4) (4x^-3y) 2. (15x^-1y^2/5xy^-4)-1 3. 24x^-1y^-2/6x^-4y^3 ... 1. (3x^2y-4) (4x^-3y) 2. (15x^-1y^2/5xy^-4)-1. 3. 24x^-1y^-2/6x^-4y^3. Best answer. 100 % (1 ...
Read More At : www.chegg.com...

### SOLUTIONS TO IMPLICIT DIFFERENTIATION PROBLEMS

SOLUTIONS TO IMPLICIT DIFFERENTIATION PROBLEMS ... + 2 y' + 3x 2 + 4x, so that (Now solve for y' .) 1 ... 1 - y - 3x 2 - 4x = (3y 2 + x + 2) y' ,
Read More At : www.math.ucdavis.edu...

### What is the simplified form of (-3x^3y^2)(5xy-1) a.) 15^2/y^2 ...

What is the simplified form of (-3x^3y^2)(5xy-1) - 1621925. 1. ... (-3)(5)} {(x^3 * x)} {(y^2 * y^-1} {-15} { x^3+1} { y^2-1} {-15} {x^4} ... Solve for x. 3.3x = 29.04
Read More At : brainly.com...

### Simple Polynomial Factoring (page 2 of 3) - Purplemath | Home

Simple Polynomial Factoring (page 2 of 3) Sections: Simple factoring, Factoring "in pairs" Factor x 2 y 3 + xy; I ... 3x 3 + 6x 2 – 15x = 3x( ) = 3x(x 2 ...
Read More At : www.purplemath.com...

### How do you implicitly differentiate xy + 3x + 5x^2 = 4 ...

... = 1y + xdy/dx = y + xdy/dx When y is differentiated WRT x in implicit ... How do you implicitly differentiate # xy + 3x + 5x^2 = 4#? ... How to solve this?
Read More At : socratic.org...

### How do you multiply 3xy(-x^4-4x^2 y+5xy^2) ? | Socratic

... (blue)(-3x^5y - 12x^3.y^2 + 15x^2y^3 color(blue)(3xy)(-x^4-4x^2y+5xy^2) =color(blue ... How do you multiply #3xy(-x^4-4x^2 y+5xy^2) #? ... How do solve #3/(x+1) ...
Read More At : socratic.org...

### Math 432 HW 2.5 Solutions

(2xnym+2 – 6xn+1ym+1) dx + (3xn+1ym+1 – 4xn+2ym) dy = 0 ... (3n – 1) – 2n = 1, and solving. . . 3(3n – 1) – 4n = 2 9n – 3 – 4n = 2 5n = 5 n = 1 m = (3 ...
Read More At : faculty.frostburg.edu...

## Suggested Questions And Answer :

### ((x)/(5y)-(1)/(4))/((3)/(4y)-(2)/(x))

x            1 ----  -    ------- 5y           4 -----------------  3         2 ---   -  ---- 4y        x find common denominators for both fractions: 4x - 5y --------- 20y ------------------ 3x - 8y --------- 4xy multiply by the reciprical of the bottom: 4x - 5y     4xy ---------  * ----------  20y         3x - 8y reduce the fractions by 4y: (4x - 5y) x --------------- 5(3x - 8y) multiply out the top and bottom: 4x^2 - 5xy ------------- 15x - 40y

### solve y= 5x+2, x=6-3y. this is systems of equations :)

Problem: solve y= 5x+2, x=6-3y. this is systems of equations :) please help me l0l 1) y = 5x + 2 2) x = 6 - 3y Substitute the value of y, from equation 1, into equation 2. x = 6 - 3y x = 6 - 3(5x + 2) x = 6 - 15x - 6 x + 15x = 6 - 15x - 6 + 15x 16x = 6 - 6 16x = 0 x = 0 Use that to solve for y. y = 5x + 2 y = 5(0) + 2 y = 0 + 2 y = 2 Check. x = 6 - 3y 0 = 6 - 3(2) 0 = 6 - 6 0 = 0 Answer: x = 0, y = 2

### -3+2(9x-5)=5(3x+2)

Problem: -3+2(9x-5)=5(3x+2) how do you solve this algebra equation? -3 + 2(9x - 5) = 5(3x + 2) -3 + 18x - 10 = 15x + 10 18x - 13 = 15x + 10 18x - 13 + 13 = 15x + 10 + 13 18x = 15x + 23 18x - 15x = 15x + 23 - 15x 3x = 23 3x/3 = 23/3 x = 23/3 Check it. -3 + 2(9x - 5) = 5(3x + 2) -3 + 2(9(23/3) - 5) = 5(3(23/3) + 2) -3 + 2(69 - 5) = 5(23 + 2) -3 + 2(64) = 5(25) -3 + 128 = 125 125 = 125 Answer: x = 23/3 = 7 2/3

### How to solve for the centroid of A(4,2), B(12,6) and C(7,13)

The three points make up a triangle. We need to find the central points of each side. This helps us to establish the medians from each corner of the triangle to the midpoint of the opposite side. The centroid will be located where the medians intersect. The sides of the triangle are AB with midpoint P; BC with midpoint Q; CA with midpoint R. P=((4+12)/2, (6+2)/2)=(8,4) Q=((12+7)/2, (13+6)/2)=(9.5,9.5) R=((7+4)/2, (13+2)/2)=(5.5,7.5) We only need two medians to establish the centroid, but it would be wise to use the third median as a double-check. We now work out the equations of the medians. Join P(8,4) to corner C(7,13): slope=(13-4)/(7-8)=-9. Intercept=4+9*8=76, and y=76-9x (using P to subsitute in equation y=-9x+b, where b is intercept). Join Q(9.5,9.5) to corner A(4,2): slope=(2-9.5)/(4-9.5)=+7.5/5.5=15/11. Intercept=2-15/11*4=-38/11 and y=1/11*(15x-38). Join R(5.5,7.5) to corner B(12,6): slope=(6-7.5)/(12-5.5)=-3/13. Intercept=6+3/13*12=114/13 and y=1/13(114-3x). Equating these three equations: 76-9x=1/11(15x-38)=1/13(114-3x) we can solve for x. 76-9x=836-99x=15x-38, so 114x=874. x=874/114=23/3 and y=7. The centroid is (23/3,7). Also, 76-9x=1/13(114-3x), so 988-117 x=114-3x and 874=114x. x=23/3 and y=7, confirming the position of the centroid.

### 3x(5x-7) -2(8x+3)

Problem: 3x(5x-7) -2(8x+3) How do i solve this problem Step by step, as always. 3x(5x - 7) - 2(8x + 3) (15x^2 - 21x) - 2(8x + 3) (15x^2 - 21x) - (16x + 6) (15x^2 - 21x) - (16x + 6) 15x^2 - 21x - 16x - 6 15x^2 - 37x - 6

### solve following system of equations

Problem: solve following system of equations solve the following system of equations: x-2y+z=6 , 2x+y-3z=-3, x-3y+3z=10 1) x - 2y + z = 6 2) 2x + y - 3z = -3 3) x - 3y + 3z = 10 Multiply equation 1 by 3. 3(x - 2y + z) = 6 * 3 4) 3x - 6y + 3z = 18 Add equation 2 to equation 4.   3x - 6y + 3z = 18 +(2x +  y - 3z = -3) -----------------------   5x - 5y      = 15 6) 5x - 5y = 15 Add equation 3 to equation 2.   2x +  y - 3z = -3 +( x - 3y + 3z = 10) ----------------------   3x - 2y      = 7 7) 3x - 2y = 7 Multiply equation 6 by 2. 2(5x - 5y) = 15 * 2 8)10x - 10y = 30 Multiply equation 7 by 5. 5(3x - 2y) = 7 * 5 9) 15x - 10y = 35 Subtract equation 9 from equation 8.   10x - 10y = 30 -(15x - 10y = 35) -------------------   -5x       = -5 -5x = -5 -5x/-5 = -5/-5 x = 1 Use equation 6 to solve for y. 5x - 5y = 15 5(1) - 5y = 15 5 - 5y = 15 5 - 5y - 5 = 15 - 5 -5y = 10 -5y/-5 = 10/-5 y = -2 Use equation 3 to solve for z. x - 3y + 3z = 10 1 - 3(-2) + 3z = 10 1 + 6 + 3z = 10 7 + 3z = 10 3z = 3 3z/3 = 3/3 z = 1 Answer: x = 1, y = -2, z = 1

### solve for x and y: 15x- 18- 2y= -3y+ y, 10x+ 7y+ 20= 4x+ 2

solve for x and y: 15x- 18- 2y= -3y+ y, 10x+ 7y+ 20= 4x+ 2 We'll work both equations to get the x and y terms on the left, and any constant value on the right. 15x - 18 - 2y= -3y + y 15x - 2y + 3y - y = 18 15x = 18 x = 18/15 x = 6/5 Now, we'll begin solving the second equation, and substitute the value of x when get to an optimal place. 10x + 7y + 20 = 4x + 2 10x - 4x + 7y = 2 - 20 6x + 7y = -18 6 * (6/5) + 7y = -18 36/5 + 7y = -18 7y = -18 - 36/5 7y = -90/5 - 36/5 7y = -126/5 y = (-126/5) * 1/7 y = -18/5

### solve 15x+24=8(10+3x)-2

solve 15x+24=8(10+3x)-2 15x + 24 = 8(10+3x) - 2 15x + 24 = 80 + 24x - 2 15x - 24x = 80 - 2 - 24 -9x = 54 x = -6

### solve for x : 15x + 34 = 3x - 9

15x + 34 = 3x - 9 15x - 3x = -9 - 34 12x = -43 x = -43 / 12